2018
DOI: 10.1016/j.stemcr.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Automated Deep Learning-Based System to Identify Endothelial Cells Derived from Induced Pluripotent Stem Cells

Abstract: SummaryDeep learning technology is rapidly advancing and is now used to solve complex problems. Here, we used deep learning in convolutional neural networks to establish an automated method to identify endothelial cells derived from induced pluripotent stem cells (iPSCs), without the need for immunostaining or lineage tracing. Networks were trained to predict whether phase-contrast images contain endothelial cells based on morphology only. Predictions were validated by comparison to immunofluorescence staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 28 publications
1
70
0
Order By: Relevance
“…It has become increasingly popular in finding latent data structures and classifying highly nonlinear datasets, attributes that are ideal for physical sciences and, more particularly, photonics 49 . Machine learning has also proven ideal for classifying cell subtypes from label-free images 85 to predict macrophage activation, 86 lymphocyte cell types, 87 pluripotent stem cell-derived endothelial cells 88 and differentiating primary hematopoietic progenitors 89 . Our analysis using a pre-trained MLP neural network clearly demonstrated that supervised machine learning can be successfully deployed to classify cells from normal and injured vessels with autofluorescence intensity as the only input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly popular in finding latent data structures and classifying highly nonlinear datasets, attributes that are ideal for physical sciences and, more particularly, photonics 49 . Machine learning has also proven ideal for classifying cell subtypes from label-free images 85 to predict macrophage activation, 86 lymphocyte cell types, 87 pluripotent stem cell-derived endothelial cells 88 and differentiating primary hematopoietic progenitors 89 . Our analysis using a pre-trained MLP neural network clearly demonstrated that supervised machine learning can be successfully deployed to classify cells from normal and injured vessels with autofluorescence intensity as the only input.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-layered neural networks that mimic a human neural circuit structure have become increasingly popular in finding latent data structures and classifying highly nonlinear photonic datasets [29]. They have also proven ideal for classifying cell subtypes from label-free images [49] to predict macrophage activation, [50] lymphocyte cell types, [51] pluripotent stem cellderived endothelial cells [52], and differentiating primary hematopoietic progenitors [53].…”
Section: Discussionmentioning
confidence: 99%
“…CNNs have also shown the capacity to accurately identify cellular states from simple transmitted-light data. For example, differentiating cells based on cell cycle stage (36), cells affected by phototoxicity (37) or stem cell-derived endothelial cells (38). Previously, researchers would generally rely in fluorescent reporters to identify these cellular features, CNNs now enable the same findings in a label-free manner.…”
Section: Cnns In Microscopymentioning
confidence: 99%
“…These methods are automatic, have high reproducibility, and are non-invasive to cells because fluorescent markers are not needed [15]. Convolutional neural networks (CNNs), which are deep learning-based networks, are capable can achieve extraordinary outcomes when applied to image analysis and identification tasks [16,17]. For example, for the identification of differentiated and undifferentiated endothelial cells, Kusumoto et al have developed a CNN-based algorithm that has an accuracy of 91.3% and an F-measure (weighted harmonic mean of the precision and the recall of the classification) of 80.9%.…”
Section: Introductionmentioning
confidence: 99%